Smart grid : linking sustainable electricity provision and consumption - Bursiewicz, Paul (2011)
This thesis examines the transformation of the US electricity grid through the integration of information and communication technology, referred to as the Smart Grid. The electricity infrastructure is explained, its historical development is analyzed, the actors instrumental in promoting its infrastructural renewal are identified, business models that promote energy efficiency for the electric utility industry are discussed, and sustainable electricity consumption is examined. The Smart Grid is found to be a necessary element for linking sustainable electricity provision and consumption in conjunction with the increased deployment of renewable energy, dynamic pricing of electricity rates, timely feedback to consumers, adequate regulatory policies, and non-price interventions in addition to market incentives to encourage energy efficiency and conservation.